Contributions of Iraqi universities in building a knowledge society - Assistant Professor Dr. Nabil Omran Musa Al-Khalidi; Researcher Saleh Shaker Hussein (Journal of the College of Education for Girls for Humanities, 2023)
Research Summary The communities have been witnessed in the current era scientifically , culturally and cognitively advanced enormously in all areas, which have evolved a leader in the community of scientific methods, including universities, which contribute to an effective contribution in building the knowledge society advanced, where universities contribute support society with human cadres possess scientific knowledge in all areas, and give it all specializations that are consistent with the need for the labor market, where it became include huge numbers of scientific minds producing knowledge and sophistication, where the impact on the social construction of communities humanity in general by profound changes in the modes of thinking and in action, behavior, character building , self-reliance of the individual social, political and economic participation Family and life interactions. The Current search derived its importance as being an attempt to increase the scientific knowledge through glances contributions to Iraqi universities in improve knowledge society, and the most recent trends to be followed by the universities for the development of university education systems in line with the requirements of the times and keep up with the global development of civilization, in order to be the main pillar in building a knowledge society.